INDIA’S ENERGY SECURITY AND CENTRAL ASIA’S ENERGY RESOURCES - DHAKA, Ambrish (CENTRAL ASIA AND THE CAUCASUS, 2006)
This century will witness the twilight of organic energy sources and perhaps the dawn of commercially successful non-organic sources. The mere truth that the former are non-renewable is a major caveat to their incessant use for future needs. This general parameter has several nuances for estimating how optimally and judiciously they can be used and how long we need to survive on them before newer technology comes to take their place. Among the most important indicators are the shifts in energy source composition and the changes in the end-sector consumption packet. These shifts and changes reflect the various production possibility curves which can be projected beyond the energy horizons. This has indeed been one of the important determinants for India in devising a cogent state of sustained energy input without too much single-handed reliance on external sources. “The Indian economy has managed to maintain its growth momentum in spite of the low rainfall during the south-west monsoon and the increase in world prices for oil and steel.”1 President of India Dr. Kalam devoted his speech on the 59th anniversary of Independence Day to India’s energy security and the challenges ahead. Since India requires 114 million tonnes of oil annually, he outlined two principles of energy security.he first focused on the efficiency mantra for cutting down losses and taking a more synergistic approach to consumption. The second principle related to tapping all the energy sources at the local, regional, and global level, which include “coal, oil, and gas supplies, until the end of the fossil fuel era, which is fast approaching.”2 “Energy Independence” is an important strategic outlook for India, which he outlined in his speech, i.e. “total freedom from oil, gas, or coal imports.” And the time period which India should set to achieve this goal is the next twenty-five years, i.e. by 2030. However, at the moment, the stage is set to increase imports not only of oil, but also of natural gas. This scenario might look quite paradoxical in view of what the president reiterated. But it is a necessary timeout, an intermediary stage on the path to attaining the ultimate goal of moving from “Energy Security” to “Energy Independence.” India’s energy-output ratio reflects the most inefficient use of energy sources. According to the World Energy Report, in 1997 the energy-output ratio amount-ed to1.04 toe per 1,000 (at 1990 prices) of the GDP, which was more than double the world av-erage.3 The main reason for this is that most of the energy needs in rural areas are met by non-commercial renewable resources and biomass which account for more than 40 percent of the total primary energy supply.